What are the main concerns related to students with disabilities as they transition from secondary schools to adult life? - Neuville, Thomas J. P., author; Lehmann, Jean P., advisor; Banning, James, committee member; Tochterman, Susanne, committee member; Brouillette, John R., committee member (Colorado State University. Libraries, 2000)
With the reauthorization of the Individuals with Disabilities Act (IDEA, 1997), lawmakers indelibly reinforced and expanded the role of the student. The capacity of the student to be self-directing and the capacity of the professional to understand all communication coming from the student determine the meaningfulness with which all educational decisions are made. Therefore, being able to know and act on the essential and distinctive characteristics of the student needs is vital to compliance with both the letter and spirit of the law. There are two purposes of this study. First, to develop theories related to or associated with characteristics of successful transition processes grounded in student concerns, and second, to develop questions for further study and learning regarding the responsibility of the transition process in secondary schools. This research expands upon previous investigations into processes of school-to-adult life transition in relation to environmental and relationship influences by focusing specifically on the essential and distinctive characteristics of student needs from the perspective of the student and discovering the processes leading to both positive and negative learning environments. This investigation was conceptualized under the paradigm of qualitative research and implemented according to grounded theory techniques. Interview respondents were parents, teachers, and students with disabilities in a private special education secondary school. Naturalistic inquiry allowed students, teachers, and parents to be interviewed while employing purposeful sampling. Students were interviewed if they were active in the transition process and expressed an interest in talking with the researcher. Teachers working with the participating students were interviewed, and parents of two students that were available were interviewed. Interview and observational data were analyzed using grounded theory coding procedures. The grounded theory includes the identification of three salient properties that students request be met in order to enhance and make practical their actual learning experience. Specifically, students increase their desire to achieve and learn when they are understood as individuals (theory of Supreme Excellence), interact in democratic educational practices, and engage in symbiotic relationships.
Pages 1 and 163 missing in number only.
Keywords: special education; social work; developmental psychology